Duel of the Discs. - Boyd, J.
Noted Japanese digital media reviewer and critic, Reiji Asakura, provides his views on the next generation of DVD recorders and players. Asakura demonstrates how the Blu-ray disc and the HD DVD formats stack up against the standard DVD. The demonstration highlighted how the video enhancement feature in the next generation players will be a bonus for early adopters and could encourage videophiles to buy early models despite such concerns as copy protection and future upgrades. However, despite the intrinsic appeal of the next generation players, consumers are discouraged from making purchase in the meantime
Keywords: Blu-ray disc; DVD players; DVD recorders; HD DVD formats; Japanese digital media reviewer; Copy protection; Next generation players; Video enhancement feature; Videophiles